The family in early modern England. Edited by Helen Berry and Elizabeth Foyster - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2009)
This collection of essays is dedicated to Anthony Fletcher, specifically selected tohighlight his contribution to the field of early modern social history. Fletcher is citedas both teacher and mentor to the editors and the book includes a short biography commemorating his work to date. The collection also marks the thirtieth anniversaryof the publication of Lawrence Stone’s The Family, Sex and Marriage, 1500–1800,and each essay is inspired by a theme that Stone addressed in his research on family history.